Child Abuse and Neglect - Fitzgerald, Michael (IntechOpen, 2022)
Child abuse and neglect are major problems facing psychiatrists, psychologists, social workers, and medical professionals. It occurs in homes and social settings and is currently increasing because of the mass displacement of families due to migration, war, and even climate change. It can be the background to so many puzzling presentations in mental health and social care settings. This book includes five chapters that address physical and sexual child abuse. Topics covered include resilience to trauma, the new psychiatric diagnosis of developmental trauma disorder, court accommodations for children with disabilities, improving teacher knowledge of child sexual abuse with training, and the global challenge of child abuse and neglect.